Analyzing Food Security Using Household Survey Data: Streamlined Analysis with ADePT Software - Moltedo, Ana (World Bank, 2015)
Since the end of the Second World War, the international community has been focusing on reducing the number and the proportion of people who suffer from hunger. Over time it became clear that no single indicator would provide a comprehensive picture of the food security situation. Rather, a suite of indicators is necessary to describe food insecurity in all its dimensions. The demand for evidence-based policies, which brings together providers such as statistical offices and users of food security indicators including policy makers and researchers, has also been increasing.